2022
DOI: 10.1109/access.2022.3147495
|View full text |Cite
|
Sign up to set email alerts
|

Toward Performing Image Classification and Object Detection With Convolutional Neural Networks in Autonomous Driving Systems: A Survey

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 265 publications
(442 reference statements)
0
10
0
Order By: Relevance
“…Data production without supervision would impact a model trained with redundant training sets. In order to recognise the environment in which predictable and unpredictable things are regarded, we must limit the data required to train the reinforcement learning model [30][31][32][33][34][35][36][37][38][39] to a set of data points.…”
Section: Related Workmentioning
confidence: 99%
“…Data production without supervision would impact a model trained with redundant training sets. In order to recognise the environment in which predictable and unpredictable things are regarded, we must limit the data required to train the reinforcement learning model [30][31][32][33][34][35][36][37][38][39] to a set of data points.…”
Section: Related Workmentioning
confidence: 99%
“…The Faster R-CNN [2] is selected for the implementation of the object detector due to being frequently used [1], [25], [46]. We choose two CNN models as the backbone network [17],…”
Section: Generalization Abilitymentioning
confidence: 99%
“…It has been shown that FPGAs outperform the other counterparts in terms of processing latency and power consumption [16], which is crucial in many autonomous applications, and in particular in Autonomous Driving Systems (ADSs) [17], [18]. At the same time, on-chip memory of automotive-grade FPGAs is limited, often amounting to less than 10MB [19]- [22] , which shows the pressing need for high-performance reduced size CNN models.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on how the radar was set up and the Doppler-FFT implementation, the Doppler processing time can range from milliseconds to dozens of milliseconds. On the other hand, neural network inference typically takes much longer and can be measured in tens or even hundreds of milliseconds [6][7][8]. Given the variety of sensors in modern automobiles, it is obvious that the CPU cannot make all decisions while still operating in real time.…”
Section: Introductionmentioning
confidence: 99%